Pengaruh Likuiditas, Profitabilitas, Solvabilitas Dan Ukuran Perusahaan Terhadap Opini Audit Going Concern Pada Perusahaan Sektor Konsumsi Yang Terdaftar Di Bursa Efek Indonesia - Shelline Angela; Dianty Putri Purba; Violyne Violyne; Dina Rosmaneliana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The purpose was to analyze the impact of liquidity, profitability, solvency and Company Size towards the Audit opinion of Going Concern. Research methods using quantitative. The population is an enterprise of enterprises of the consumption sector, and sampling is determined by the method of purposive sampling. Data analysis using multiple linear regression analysis. The results of partial hypothesis testing that liquidity, profitability and no impact on the Audit opinion Going Concern, but only size company has an effect on the Audit opinion Going Concern and while simultaneously that liquidity, profitability, solvency and size company simultaneously not impact Audit opinion Going Concern. Keywords: Liquidity, Profitability, Solvency, Size Company, Audit Opinion Going Concern